Enhancement of Power Harvesting by Tuning Moment of Inertia - Shahenda Mohamed; Ebtisam Abdel-Gwad (Port Said Engineering Research Journal, 2021)
This investigation examines the design of an innovative independent mechanism for tuning the resonant frequency and thus generate greater amounts of energy. The proposed concept is based on adjusting the resonant frequency by automatically modifying the mass moment of inertia. A frequency tuning algorithm is used to maintain the system in the case of resonant continuously, and that by change the proof mass position within the tuning range. The electromagnetic energy harvester is used to convert the vibration energy into electrical energy. The proposed design is analyzed using the methodology of approximate single degree of freedom system to study the effect of the mass position on Eigen-frequency and also to determine the response of the system as well as the harvested power. Analytical results were confirmed and verified to high accuracy with laboratory results. It is worth mentioning that this proposed design is suitable for low frequencies and can be considered as a good step towards the production of autonomous energy harvesters.